Strontium titanate (SrTiO3) mesoporous coatings for enhanced strontium delivery and osseointegration on bone implants - Escobar, Ane (2019)
The incorporation of strontium (Sr) in titania enhances surface bioactivity and has a positive effect on pre-osteoblastic cell attachment, proliferation, and differentiation. Strontium titanate mesoporous films (SrTiMFs) with 30% pore volume and a 20% Sr molar content have been prepared by the evaporation induced self-assembly method. SrTiMFs display a large internal surface area available for exchange of Sr, which is released in cell media up to 44% within the first 8 h. SrTiMFs improve attachment of MC3T3-E1 pre-osteoblastic cells, which show larger filopodia and more elongated features than cells attached to plain mesoporous titania films (MTFs). SrTiMFs also display improved cell proliferation and differentiation rates indicating that overall Sr incorporation into mesoporous titania coatings can lead to enhanced osseointegration during the early stages of bone tissue formation.